Faktor – Faktor Yang Mempengaruhi Terjadinya Infertilitas Primer Pada Pasangan Usia Subur Di Puskesmas Pegajahan Kec. Pegajahan Kab. Serdang Bedagai Tahun 2023 - Ernawati Napitupulu; Isyos Sari Sembiring; Titin Suherni; Elnia Elnia; Rizky Andriani (Jurnal Ventilator, 2023)
BACKGROUND The exact incidence of infertility is not yet known with certainty, it varies greatly depending on geographical conditions, culture and social status of the country. Women who marry at an old age or mature and work actively will greatly affect a woman's fertility. It is estimated that around 2 million new infertile couples appear every year and this number continues to increase. It is estimated that a healthy couple will get fertilized within 1 year (Nuparma, 2017). Infertility data in the world according to the World Health Organization (WHO) and other reports estimates that 8-12% of couples experience infertility problems during their reproductive years. If eight percent of the global population figure is around 60-80 million couples who have not had children. OBJECTIVE To analyze the factors that influence the occurrence of primary infertility in couples of childbearing age at the Pegajahan Community Health Center, Pegajahan District, Serdang Bedagai District in 2023. METHOD chi square test p value < 0.05 means H0 is rejected and Ha is accepted, the statistical test results show a significant relationship. RESULTS: There is a significant relationship between age, menstrual cycle and no history of PMS and employment with the incidence of infertility and is a risk factor that has a significant influence on the incidence of infertility. Suggestions are given for research and for research sites and for educational institutions regarding exclusive breastfeeding and the implementation of IMD for newborn babies